Інформаційна технологія вирішення задачі аналізу несправностей технічних виробів - Мащенко, А. Р. (ХНУРЕ, 2024)
This work explains the information technology employed for dealing with analysis of technical products’ defects. Three analytical methods are explored: descriptive statistics, time series analysis, and linear programming. Descriptive statistics provide a comprehensive overview of key performance indicators, offering insights into the central tendency and variability of service centre data. Time series analysis enables the examination of temporal patterns and trends, aiding in forecasting future demands. Additionally, the article explores the application of linear programming to optimize service centre operations by identifying the most efficient allocation of resources.
Keywords: несправність технічних виробів; технічний виріб